Porous barriers? Assessment of gene flow within and among sympatric long‐eared bat species. Issue 24 (7th December 2018) - Andriollo, Tommy; Ashrafi, Sohrab; Arlettaz, Raphaël; Ruedi, Manuel
Abstract: Species are the basic units for measuring biodiversity and for comprehending biological interactions. Yet, their delineation is often contentious, especially in groups that are both diverse and phenotypically conservative. Three cryptic species of long‐eared bats, Plecotus auritus, P. austriacus, and P. macrobullaris, co‐occur over extensive areas of Western Europe. The latter is a fairly recent discovery, questioning the overall diversity of the entire Plecotus complex. Yet, high morphological and acoustic similarities compromise the reliable identification of long‐eared bats in the field. We postulate that such extensive phenotypic overlap, along with the recurrent observation of morphologically intermediate individuals, may hide rampant interspecific hybridization. Based on a geographic sampling centered on areas of sympatry in the Alps and Corsica, we assessed the level of reproductive isolation of these three Plecotus species with mitochondrial and nuclear markers, looking at both inter‐ and intraspecific genetic population structuring. No sign of hybridization was detected between these three species that appear well separated biologically. Genetic structuring of populations, however, reflected different species‐specific responses to environmental connectivity, that is, to the presence of orographic or sea barriers. While the Alpine range and the Ligurian Sea coincided with sharp genetic discontinuities in P. macrobullaris and P. austriacus, the more ubiquitous P. auritus showed no significant population structuration. There were clear phylogeographic discrepancies between microsatellite and mitochondrial markers at the intraspecific level, however, which challenges the reliance on simple barcoding approaches for the delineation of sound conservation units. Abstract : In Western Europe, three long‐eared bat species pose important difficulties of identification, that could be explained by either ancient or ongoing hybridization. We show, with a combination of markers, there is no gene flow between species as no hybrids have been evidenced. Although they exhibit a highly cryptic morphology, these bas show idiosyncratic responses to barriers to gene flow represented by the Alps and the Ligurian Sea.